ESTILO DE VIDA DE MULHERES PÓS-MENOPAUSA EM UM MUNICÍPIO DA REGIÃO NOROESTE DO RS - Leite, Marines T.; Berlezi, Evelise M.; Bottaro, Silvania M.; Battisti, Iara D. E.; Franco, Rosecler R.; Bertolo, Elvio M. (Salão do Conhecimento, 2013)
Resumo